Initial validation of a self-report measure of perceptions of interpersonal attraction. (February 2015) - Riggio, Heidi R.; Lui, P. Priscilla; Garcia, Amber L.; Matthies, Brigitte K.; Culbert, Gar; Bailey, Jessica
Highlights: We examine psychometric properties of a self-report measure of interpersonal attraction. Factor analysis indicates two factors of Attraction To and Attraction From others. Perceptions of attraction are correlated with personality traits and social skills. Perceptions of attraction predict desirability of alternatives to romantic relationships. Abstract: We examine psychometric properties and validity of the Perceptions of Attraction scale ( POA ). Responses of undergraduate students ( N  = 510) indicate that the POA has high reliability and a coherent factor structure comprising two dimensions of feelings of attraction toward others and perceptions of attraction from others that explain 67% of response variance. POA scores are correlated with social skills and extraversion, but not related to other personality dimensions. POA scores are predictive of outcomes in current romantic relationships ( n  = 160).